What is the second derivative of f(x)=-csc^2x f(x)=csc2x?

1 Answer
Mar 2, 2017

-2csc^2(x)-6cot^2(x)csc^2(x)2csc2(x)6cot2(x)csc2(x)

Explanation:

cscx = 1/sinxcscx=1sinx

so

-csc^2x = -1/sin^2xcsc2x=1sin2x

Using the quotient rule, we know that

d/dx f(x)/g(x) = (f'(x)g(x)-g'(x)f(x))/g^2(x)

If we say that f(x)=-1 and g(x)=sin^2(x), then

f'(x)=0

g'(x)=2sin(x)cos(x)

and, putting these into the quotient rule formula,

d/dx f(x)/g(x) = (--1*2sin(x)cos(x))/sin^4(x)

=(2cos(x))/sin^3(x)

This gives the first derivative.

The second derivative is the derivative of the first derivative, so do the whole process again.

Use new f(x) = 2cos(x) and g(x)=sin^3(x).

f'(x)=-2sin(x)

g'(x)=d/dx(sin^2(x)*sin(x)) =

d/dxsin^2(x)*sin(x)+sin^2(x)*d/dxsin(x)=

2sin(x)cos(x)*sin(x)+sin^2(x)*cos(x)=3sin^2(x)cos(x)

so

g'(x)=3sin^2(x)cos(x)

Now, using the formula for the quotient rule,

d/dx f(x)/g(x) = (f'(x)g(x)-g'(x)f(x))/g^2(x)

=(-2sin^4(x)-6sin^2(x)cos^2(x))/sin^6(x)

=-2/sin^2(x)-(6cos^2(x))/sin^4(x)

=-2csc^2(x)-6cot^2(x)csc^2(x)